Rhizobacteria in growth and quality of acai seedlings - Campos, Thiago Souza [UNESP] (2023)
The success of any plant development relies on healthy and vigorous seedlings, and the use of rhizobacteria is a sustainable alternative for the production of high-quality seedlings as they positively interfere in plant development. Thus, the objective of this study was to evaluate the effect of rhizobacteria on growth and quality of seedlings of agai (Euterpe oleracea Mart.), a native palm of Brazil, which has significant ornamental value in addition to the ecological and economic role, mainly by providing sweet heart of palm and fruit pulp. The experimental design was entirely randomized. There were five treatments (Bacillus subtilis, Bacillus megaterium, Bacillus amyloliquefaciens and Azospirillum brasilense plus the absence of microorganisms -control); four replicates and ten plants per plot. The following characteristics were evaluated: shoot height (cm), root length (cm); stem diameter (mm); number of leaves; leaf area (cm2); shoot, and root as well as total dry matter (g). Shoot/root ratio was determined and Dickson Quality Index. The data were submitted to variance analysis and the means were compared using Tukey's test at 5% probability. Pearson's correlation matrix was also determined. The rhizobacterium Bacillus subtilis provided higher growth while Bacillus amyloliquefaciens provided lower growth and quality of agai seedlings.